Tidal breathing patterns derived from structured light plethysmography in COPD patients compared with healthy subjects - Motamedi-Fakhr, Shayan; Wilson, Rachel C.; Iles, Richard (Medical devices (Auckland, N.Z.), 2017)
Differences in tidal breathing patterns have been reported between patients with chronic obstructive pulmonary disease (COPD) and healthy individuals using traditional measurement techniques. This feasibility study examined whether structured light plethysmography (SLP) - a noncontact, light-based technique - could also detect differences in tidal breathing patterns between patients with COPD and healthy subjects. A 5 min period of tidal (quiet) breathing was recorded in each patient with COPD (n=31) and each healthy subject (n=31), matched for age, body mass index, and sex. For every participant, the median and interquartile range (IQR; denoting within-subject variability) of 12 tidal breathing parameters were calculated. Individual data were then combined by cohort and summarized by its median and IQR. After correction for multiple comparisons, inspiratory time (median tI) and its variability (IQR of tI) were lower in patients with COPD ( <0.001 and <0.01, respectively) as were ratios derived from tI (tI/tE and tI/tTot, both <0.01) and their variability ( <0.01 and <0.05, respectively). IE50 (the ratio of inspiratory to expiratory flow at 50% tidal volume calculated from the SLP signal) was higher ( <0.001) in COPD while SLP-derived time to reach peak tidal expiratory flow over expiratory time (median tPTEF /tE) was shorter ( <0.01) and considerably less variable ( <0.001). Thoraco-abdominal asynchrony was increased ( <0.05) in COPD. These early observations suggest that, like traditional techniques, SLP is able to detect different breathing patterns in COPD patients compared with subjects with no respiratory disease. This provides support for further investigation into the potential uses of SLP in assessing clinical conditions and interventions.